Procura de metodologia municipal para a reabilitação de espaços urbanos - Ferreira, Maria Fernanda Dias (2011)
O presente trabalho propõe-se reunir o conhecimento indispensável para o processo de reabilitação de espaços urbanos em declínio, particularmente nos contextos em que a presença de património urbano exige maior ponderação nas decisões. Com este objectivo, traça um percurso evolutivo do quadro teórico-prático, de modo a confrontá-lo com experiências concretas, para aprender as melhores práticas e identificar questões-chave. Através da análise de diplomas do quadro legal para a reabilitação urbana e em função de uma síntese global, procura responder à questão: “Quais os conhecimentos fundamentais na actualidade, para viabilizar iniciativas de reabilitação urbana em Portugal?”. Avança também com recomendações metodológicas e operativas para que o objectivo seja atingido. ABSTRACT: The purpose of this work is to aggregate fundamental knowledge necessary to the rehabilitation processes of urban areas in decline. Intending to support action, it studies particularly those areas contextualised by the presence of urban cultural heritage, which requires further considerations on decisions to make, Having this objective in mind, this work traces the evolutional path of the theoretical-practice framework, in order to confront him with real experiences, for learning the best practices and indentifying key-issues. Through the review of legal issues coming from the Portuguese legislation for urban rehabilitation, as well by making a synthesis between old and existing knowledge on the subject, this work intends to answer the following question: What is the fundamental knowledge necessary to make decisions and to implement actions on this matter? It also sets out operative and methodological recommendations in order to achieve the goal.